Inflammatory bowel disease in the West Indies. Issue 6194 (6th October 1979) - Bartholomew, C; Butler, A
Abstract : Inflammatory bowel disease is generally assumed to be rare among negroes and Indians. Over 10 years 34 cases of ulcerative colitis and 14 cases of Crohn's disease were seen in one medical and one surgical unit in Port-of-Spain, Trinidad. Twenty-six patients were Negroes, 18 were Indians, three were of mixed race, and one was Caucasian. In many of these patients the disease was extensive and several of those with Crohn's disease suffered severe complications. The assumption that inflammatory bowel disease is rare among West Indians of African and Indian origin therefore seems to be wrong.